EFEK TERAPI HORMON OODEV TERHADAP PERKEMBANGAN TINGKAT KEMATANGAN GONAD IKAN KAKAP MERAH (Lutjanus sp.) DI TELUK TALENGEN - Aprelia Tomasoa; Usy Nora Manurung; Sermiati Makasehe; Christania Daukalu; Jelia Janica Makarilang; Srimayangsari Balandatu (Pusat Penelitian dan Pengabdian Pada Masyarakat, Politeknik Negeri Nusa Utara, 2021)
Marine aquaculture activities in the Sangihe Islands, more specifically in the waters of Talengen Bay, are not yet optimal and still utilize seeds from catches in nature. This study aims to determine the effect of using the Oodev hormone and obtain the best dose to stimulate the gonadal maturity level (TKG) of red snapper (Lutjanus sp.). The red snapper used comes from the catch in the waters of Talengen Bay and is also domesticated in floating net cages. The sampled fish used were 60 individuals with average body weight (30.5 g). The Oodev hormone dose treatment, namely; 0 mL/kg, 0.5 mL/kg, 1 mL/kg and 1.5 mL/kg. Oodev hormone was applied to commercial feed specifically for marine fish with the trademark Megami GR-3 orally for 30 days of rearing. The results showed that the administration of the Oodev hormone had a positive effect on the gonadal maturity level of red snapper, with the development of different levels of gonadal maturity in each treatment. The 0.5 mL/kg dose treatment resulted in the highest gonadal maturity level (TKG III). The maturation stage was followed by 1 mL/kg and 1.5 mL/kg (TKG II) treatments. Meanwhile, compared with the 0 mL/kg treatment, the developmental stage was still TKG I (immature). These findings provide Oodev hormone with 0.5 mL/kg dose could stimulate the red snapper gonad maturity level to mature for 30 days of rearing.